Model Kesetimbangan Pada Adsorbsi Ion Zn2+ Menggunakan Partikel Tricalcium Phosphate Sebagai Adsorben - Dovy Reyandi; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zinc metal pollution (Zn2+) can result in negative impacts on people's life. One effort to reduce the content of zinc metal that is the adsorption process. The objective of this research is to study the effect of temperature and string rate as well as determination of equilibrium model in the zinc ion adsorption using tricalcium phosphate (TCP) as the adsorbent. Zinc (Zn+2) solution with 3 mg/l was added with 1 g of TCP in a glass beaker with stirring rate of 100 rpm, 200 rpm, and 300 rpm at temperature 30°C, 40°C and 50°C. Zinc concentration in the liquid was analyzed using AAS. The adsorption temperature decreased when the adsorption capacity of TCP (Qe) increased. The calculation result of absorption capacity (Qe) at stirring rate of adsorption 100 rpm at temperature of adsorption 30°C, 40°C and 50°C were Qe 1.0133 mg/g, 0.9598 mg/g and 0.8771 mg/g respectively. The adsorption capacity (Qe) of adsorbent TCP increased as stirring rate adsorption increased. The adsorption capacity (Qe) of zinc at temperature adsorption 30°C for stirring rate of 300 rpm, 200 rpm, and 100 rpm were 1.3702 mg/g, 1.3426 mg/g, and 1.3047 mg/g respectively. Adsorption mechanism of zinc (Zn2+) with TCP is suitable with Freundlich isotherm model.Keywords: adsorption, zinc (Zn2+), equilibrium model, tricalcium phosphate